Analysis of the Benefits of Implementation of IPD for Construction Project Stakeholders - Mahdi Alinezhad; Ehsan Saghatforoush; Zahra Kahvandi; Christopher Preece (Salehan Institute of Higher Education, 2020)
The greatest challenges for construction infrastructure projects are those related to increasing problems of managing the time and cost in project implementation. For many years, new methods have been used to reduce the problems to do with separation of design from the implementation stage. An important point is that all projects tend to require integration; however, it has been observed that construction projects usually enjoy the benefits and capacities of updated methods and technologies later than other industries. One of these approaches, which have been growing in developed countries for some time, is using the Integrated Project Delivery (IPD) approach. Using such an approach has various benefits, but also would seem to pose significant challenges. To-date, it and has not still achieved success in terms of legal recognition and wider implementation. The aim of this study is to extract the benefits of the implementation of the IPD approach using an in-depth literature review. Then descriptive analysis is applied to identify the benefits of IPD. The benefits of applying this approach for key construction project stakeholders are classified using pattern analysis. This study has offered a framework in order to present available generic and specific benefits to each project stakeholder, and it provides the required motivation for project owners to use and implement it in their future projects. Moreover, they should understand the important factors that lead to IPD adoption. They can use this information to develop a contractual framework to make it more effective.